Antitumor Activity of Diospyros peregrina on Ehrlich Ascites Carcinoma in Mice - Raju, A. B.; Y, Venu Gopal; A, Ravindranath; G, Kalpana; V, Prabhakar Reddy (Journal of Scientific Research, 2011)
The methanol extract of Diospyros peregrina (Ebenaceae) bark (MEDP) were evaluated for antitumor activity against Ehrlich ascites carcinoma (EAC)-bearing swiss albino mice. The extract was administered at the doses of 200 and 400 mg/kg body weight per day for 14 days after 24 h of tumor inoculation. After the last dose and 18 h fasting, the mice were sacrificed. The present study deals with the effect of MEDP on the growth of transplantable murine tumor, life span of EAC-bearing hosts and hematological profile MEDP caused significant (P < 0.01) decrease in tumor volume, packed cell volume, and viable cell count; and it prolonged the life span of EAC-tumor bearing mice. Hematological profile converted to more or less normal levels in extract-treated mice. The results indicate that MEDP exhibited significant antitumor activity in EAC-bearing mice. Keywords: Diospyros peregrina; Ehrlich ascites carcinoma; Antitumor. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.6787 J. Sci. Res. 3 (2), 413-419 (2011)